Economic Development of Mangosteen Agro-Industry Based on Sustainability - Oryzanti, Parwa; Rustiadi, Ernan; Eriyatno, Eriyatno; Rochman, Nurul Taufiqu (Universitas Negeri Semarang, 2019)
The concept of developing agro-industry based agropolitan area for Mangosteen Peel Extract isÃ‚Â a solution to create the high added value and to increase peopleÃ¢â‚¬â„¢s income in the area. Agro-industry development in agropolitan areas by optimizing the local strategic commodities is a breakthrough to supportÃ‚Â the regional economy growth to be sustainable, so it is common in accordance with the potential regional leading commodities. The aim of this research is to analyze the sustainability of the area and to assess the feasibility of mangosteen agro-industry investment. The results of analysis show that the level of sustainability of technological and infrastructure, economic, social, and environmental and technological aspects are categorized as less sustainable with the sustainability index ranging from 34.12% to 49.96%. While the policy aspects in the development of Karacak agropolitan area are categorized as unsustainable with the sustainability index of 22.31%. The results of the feasibility analysis show that the capsulated agro-industrial product of mangosteen peel extract have greater opportunity to attract the investors because it is feasible with NPV value of Rp 17,690,067,855 and the added value of Rp 90,833/ kg of raw materials.